PENINGGALAN ARKEOLOGI MASA AWAL HOLOSEN DI KAWASAN GUNUNG TUKUM LEMBAH BALIEM KABUPATEN JAYAWIJAYA - Maryone, Rini (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
apua is the eastern end of Indonesia, who inhabited the coastal areas to the mountains with abundant diversity of archaeological remains, both from the Pleistocene to the Holocene. From the research that has been conducted by the Institute for Archaeology Jayapura, the cultural remains of Pleistocene danholosen in the Mountains High. These sites include the area in the district of Mount Tukum Jayawijaya. Research in the area surrounding Mount Tukum and there are a number of archaeological remains in the form of natural cave site, location of cutting pork, pork burning locations and there are a number of artifacts that human bones, handheld axe Baliem types I, II, pelandas stone materials, stone axe makers of materials quartz sand, stone and granite grindstones. Based on the survey to review the components of the environment there is still a gap which still has not found a review of biological components (ecofak) that characterizes the end of life plestosen. But characterize some of the artifacts found at the pattern of human life during the Holocene.